THE EFFECT OF PREMIUM PRICES AND BRAND IMAGE ON THE DECISIONS OF SHARIA ‎INSURED CUSTOMERS - Syarif, Hazas; Bahrudin, Moh.; Tamara, Oktia (Al-Mashrof: Islamic Banking and Finance, 2020)
This research is based on the problem of decreasing the number of customers of Prudential Syariah Insurance Lampung Branch from 2016-2018, where this is inversely proportional to the Prudential Sharia Insurance of Indonesia. In making a product purchase, premium prices and brand image are considered as important factors as an assessment of a product. This study aims to determine whether there is an influence of premium prices and brand image on the decisions of sharia insurance customers, where this research was conducted on Prudential Sharia Insurance customers.This research uses quantitative methods, data collection uses interviews and questionnaires. While sampling using purposive sampling and accidental sampling techniques and got a sample of 42 respondents, Then test the instrument using the validity test, reliability test, and proceed to the classic assumption test and hypothesis test. The results of this study obtained the value of Thitung for each variable, namely the premium price (X1) of 5.461> 2.021 (Ttable) with a significance value of 0.000 and brand image (X2) of 1.318 <2.021 with a significance value of 0.175. Based on the results of the analysis that has been done, it can be concluded that from the two independent variables that significantly influence the dependent variable, only the premium price variable has a positive effect, which is 5.461 with a Sig 0.000 level.